How mentoring helped a young agripreneur get started in Nigeria - Blessing, Mene (Technical Centre for Agricultural and Rural Cooperation, 2018)
Young Agripreneur, Mene Blessing, from Nigeria, has been mentored through different youth programme. he shares how his mentorship experience has been impactful for his professional growth.